2016
DOI: 10.1007/s13277-016-5402-6
|View full text |Cite
|
Sign up to set email alerts
|

Lentivirus-mediated silencing of HSDL2 suppresses cell proliferation in human gliomas

Abstract: Gliomas are the most common type of malignant brain tumors, and the related prognosis is poor. Though many genes have been identified as factors in the development and progression of gliomas, underlying mechanisms remained unclear. It was clear that abnormal lipid metabolism was one of the major hallmarks of cancers. However, few factors associated with lipid metabolism have been reported to be involved in cancer pathogenesis. Hydroxysteroid dehydrogenase-like 2 (HSDL2) is a protein containing sterol carrier p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 25 publications
4
50
0
1
Order By: Relevance
“…The production of lentivirus and cell infection was performed as described in previous studies ( Ruokun et al, 2016 ; Song et al, 2016 ). The expression of Zebrafish Calr plasmid was based on the lentivirus vector pCDH-CMV-MCS-EF1-Puro.…”
Section: Methodsmentioning
confidence: 99%
“…The production of lentivirus and cell infection was performed as described in previous studies ( Ruokun et al, 2016 ; Song et al, 2016 ). The expression of Zebrafish Calr plasmid was based on the lentivirus vector pCDH-CMV-MCS-EF1-Puro.…”
Section: Methodsmentioning
confidence: 99%
“…Results from in vitro experiments disclosed that HSDL2 KD inhibited the growth and metastasis of lung adenocarcinoma. Several previous studies investigating the effects of HSDL2 in other malignant tumors have also confirmed the anti-tumor effects of HSDL2 KD [20][21][22][23]. But unfortunately, the molecular mechanism underlying the role of HSDL2 on tumor progression has not been further explored in these studies.…”
Section: Discussionmentioning
confidence: 94%
“…Studies have shown that the role of HSDL2 in tumor progression is complex and influenced by the type of tumor. HSDL2 has promoting effects on tumor progression in papillary thyroid cancer [20], bladder cancer [21], ovarian cancer [22], and glioma [23], but has suppressing effects in cholangiocarcinoma [24]. At present, the role of HSDL2 in the progression of NSCLC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…), but HSDL2, IST1 and PABPC1 could also play important roles in KLF5‐mediated tumor growth, which remains to be clarified. For example, silencing the HSDL2 orphan short‐chain dehydrogenase suppresses cell proliferation in glioma, and the polyadenylate binding protein PABPC1 interacts with and stabilizes a lncRNA that appears to promote tumor growth and metastasis of human gallbladder cancer . KLF5 regulates a number of cellular processes, so many potential KLF5‐interacting nuclear proteins provide candidates for further characterization for their interactions with KLF5 to regulate different cellular processes.…”
Section: Discussionmentioning
confidence: 99%